The influence of English club activities to understand the reading of procedure texts at classroom learning of SDN Mimbaan IV Situbondo - Mohammad Arief Wahyudi; Mohammad Kurdi Wijaya; Ihwan Firmasyah (Universitas Madura, 2026)
To improve the quality of education, a well-planned learning system is needed, including extracurricular activities such as English clubs, which help students increase their knowledge and language skills outside of class hours. The research focused on third-grade students at SDN Mimbaan IV Situbondo who had difficulty understanding procedural texts due to their limited vocabulary. Getting the solution above, the researcher introduced program English club activity, so appear the statement like: Is there any significant effect of English club activities to understand the reading of procedural texts at third grades students of SDN Mimbaan IV? To answer these questions the researcher used quantitative in pre- experimental that consisted of 15 students in one classroom. From the analyses data, the results of the One-Sample t-Test showed a Sig. (2-tailed) value of 0.000, less the an 0.05. The post-test mean was 91.60, with a mean difference of 16.600 compared to the reference value of 75. Because Sig. <0.05, H₁ is accepted and H₀ is rejected so there is a significant effect of English club activity to understand the reading of procedure texts at the Third Grades Students of SDN Mimbaan IV. So, the conclusion that English club activity has a significant effect to understand in reading of procedure texts at the Third Grades Student of SDN Mimbaan IV Situbondo.